Mindful sport performance enhancement with an American college rugby team: a consensual qualitative research study - Minkler, T. O.; Hut, M.; Glass, C. R.; Thomas, H. M.; Weppner, C. H.; Flannery, C. B. (The Sport Psychologist, 2025)
Mindfulness-based interventions are a popular form of mental training for athletes. Because most existing research relies on quantitative methods, the present study explored student-athletes` experiences with mindfulness training, specifically mindful sport performance enhancement, using postintervention interviews and the consensual qualitative research protocol. A secondary focus examined potential differences based on intervention session scheduling. Ten male college rugby players were interviewed after participating in mindful sport performance enhancement either before or after rugby practice. Results indicated that athletes enjoyed exercises involving movement and informal mindfulness and reported sport-related benefits for self-regulation, awareness, and acceptance following mistakes. They also described increased present-moment attention and awareness in their daily lives, nonjudgmental reactions, and better stress coping. Additionally, athletes shared challenges related to session length, staying focused, establishing a practice routine, and managing distractions at home. Integrating mindful sport performance enhancement before sport practice reportedly helped with mental/physical readiness, whereas postpractice integration helped more with physical recovery and relaxation.